2014
DOI: 10.1093/infdis/jiu093
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of CD4+ and CD8+ T-cell Responses to Cytomegalovirus in HIV-Infected and HIV-Uninfected Men Who Have Sex With Men

Abstract: Studies of T-cell immunity to human cytomegalovirus (CMV) primarily reflect anti-CMV pp65 or immediate early antigen 1 (IE-1) activity. We assessed responses of T cells from human immunodeficiency virus (HIV)-negative and HIV-infected men to peptide pools spanning 19 CMV open reading frames selected because they previously correlated with total CMV-specific T-cell responses in healthy donors. Cells producing cytokines in response to pp65 or IE-1 together composed <12% and <40% of the total CD4(+) and CD8(+) T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 15 publications
4
33
0
Order By: Relevance
“…36 Furthermore, CMV cell-mediated immune responses to the pp65 peptide pool may underestimate total T cell responses against CMV. 37 Thus, the reason for discordance between cellmediated and humoral responses in our HIV-infected participants cannot be entirely explained and further investigation is needed.…”
Section: Cd38mentioning
confidence: 88%
“…36 Furthermore, CMV cell-mediated immune responses to the pp65 peptide pool may underestimate total T cell responses against CMV. 37 Thus, the reason for discordance between cellmediated and humoral responses in our HIV-infected participants cannot be entirely explained and further investigation is needed.…”
Section: Cd38mentioning
confidence: 88%
“…This virus, which is highly prevalent in both the geriatric population and HIV+ persons, may cause clonal T-cell expansion, leading to immune activation and chronic inflammation with their associated adverse health outcomes (7579). The potential importance of CMV in the pathogenesis of systemic inflammation is supported by the fact that it is the target for a very large proportion of circulating T cells in both HIV− and HIV+ people, which is often greater than 10% and can be 30–40% (for example,(80)(81;82)).Some studies have found a direct association between positive CMV serology and frailty and functional decline in the elderly (49;83), but data are conflicting (84;85). …”
Section: Chronic CMV Infection Frailty and Hiv Infectionmentioning
confidence: 99%
“…These findings support the hypothesis that chronic CMV infection is correlated with immune activation. Although CMV infection is common in people infected with HIV, and a very large proportion of the T-cell repertoire is devoted to CMV in HIV-infected persons, even those on long term HAART, (39;81;82), it remains to be determined if CMV-induced immune responses are quantitatively related to systemic levels of inflammation or to frailty in either HIV+ or HIV− populations.…”
Section: Chronic CMV Infection Frailty and Hiv Infectionmentioning
confidence: 99%
“…Among HIVinfected and uninfected MSM participants in the MACS, we conducted an extensive study of T cell responses to peptide pools encoded by 19 HCMV ORFs that elicited the largest responses (correlation of 0.9 with total responses) in healthy donors. Our results demonstrate that T cell responses to pp65 and IE1 combined only represented <12% of the total CD4 + and <40% of the total CD8 + T cell responses (Li et al 2014a), suggesting the need for more comprehensive evaluation of the impact of chronic HCMV infection on T cell immunity beyond the commonly tested HCMV pp65 and IE1 epitopes.…”
Section: Chronic CMV Infection In Older Adults: Diagnostic Evaluationmentioning
confidence: 86%